PENINGKATAN KAPASITAS MASYARAKAT MENGENAI LUKA BAKAR MELALUI “JADIAN” (JAGA DIRI DAN LINGKUNGAN, YUK KENAL LEBIH DALAM TENTANG LUKA BAKAR) - Sandra Pebrianti; Andry Tanta Pramudya; Bambang Aditya Nugraha (LP4M STIKes Karsa Husada Garut, 2023)
Background: Burns are a form of trauma that occurs as a result of human activities in the household, industry, traffic accidents, and natural disasters. There are people's habits that are not appropriate in handling first aid in cases of burns. It can be seen that the incidence of burns in the community is still quite high and the level of public knowledge about first aid for burns is still low. It is important to do health education to increase knowledge of the dangers of burns and first aid in accidents. Objective: The aim of this health education is to increase knowledge about burns and the ability to manage first aid in burn injuries. Sample: The target of this health education activity is the general public, especially risk groups, which are held online. Method; The method used in health education is lecture and question and answer. Results: Realization of solutions to prevent and provide appropriate care for burns independently at home can be done by providing health education regarding burn prevention and self-care at home after hospitalization so as not to exacerbate the condition of burns. This effort is one of the efforts to provide education to add insight and build public awareness regarding personal health, namely preventing burns and carrying out post-hospitalization independent care at home. Conclusion: Health education activities are one of the efforts to provide education to add insight and build awareness of personal health related to preventing burns and carrying out independent care after hospitalization at home.